2019
DOI: 10.1080/02640414.2019.1642052
|View full text |Cite
|
Sign up to set email alerts
|

Performance Nutrition in the digital era – An exploratory study into the use of social media by sports nutritionists

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(47 citation statements)
references
References 30 publications
7
36
2
Order By: Relevance
“…More research is needed on the effect of the sports RD separate from other behaviors to determine best practices to increase their effectiveness. Though these other nutrition support options can help the athletes, a sports RD is needed on staff in order to ensure the training table is meeting each athlete’s needs and nutrition information spread through these other options, such as social media, is adequate and appropriate [ 43 ]. There has been a lack of structure for how a sports dietitian aids their athletes due to the recent creation of the position, but there have been efforts by the professionals in the field to further standardize their practice [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…More research is needed on the effect of the sports RD separate from other behaviors to determine best practices to increase their effectiveness. Though these other nutrition support options can help the athletes, a sports RD is needed on staff in order to ensure the training table is meeting each athlete’s needs and nutrition information spread through these other options, such as social media, is adequate and appropriate [ 43 ]. There has been a lack of structure for how a sports dietitian aids their athletes due to the recent creation of the position, but there have been efforts by the professionals in the field to further standardize their practice [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…For both journals, not a single article title included the terms "sentiment analysis" or "opinion mining." Even for the term "social media," only one survey on the use of social media by sports nutritionists in the Journal of Sports Sciences [15] and an editorial explaining the increased use of social media by the European Journal of Sports Sciences [16] were found. A search for the terms "sentiment analysis" or "opinion mining" in the Web of Science Core Collection resulted in 1114 articles, but not a single article resulted when filtering for the Web of Science Category "sport sciences."…”
Section: Introductionmentioning
confidence: 99%
“…From the research that has been done, it has been found that female athletes are more likely to use social media for nutrition purposes and athletes commonly used social media for practical nutrition purposes related to recipes or information about restaurants (Bourke et al, 2019). Sports nutritionists have been encouraged to embrace social media and to utilize it for interventions to their athletes (Dunne et al, 2019). With the majority of college athletes reporting they interacted with the posts on Instagram and retaining the information, this indicates using social media may be beneficial for sports nutritionists and dietitians to educate their athletes.…”
Section: Protein Knowledge Related To Year In School and Sportmentioning
confidence: 99%
“…When specifically looking at sports performance nutrition, a research study explored how sports nutritionists utilized social media as a part of their nutrition services and also their experiences and opinions of social media's use in practice (Dunne et al, 2019). This study surveyed sports nutritionists and had voluntary follow-up interviews.…”
Section: Education Via Social Mediamentioning
confidence: 99%
See 1 more Smart Citation